Carbon assimilation in upper subtidal macroalgae is determined by an inverse correlation between Rubisco carboxylation efficiency and CO2 concentrating mechanism effectiveness - Capó-Bauçà, Sebastià; Galmés, Jeroni; Aguiló-Nicolau, Pere; Ramis-Pozuelo, Sonia; Íñiguez Moreno, Concepción (Wiley, 2023)
Seaweeds have a wide ecophysiological and phylogenetic diversity with species expressing different Rubisco forms that frequently coexist with biophysical CO2 concentrating mechanisms (CCMs), an adaptation that overcomes the low CO2 availability and gas diffusion in seawater. Here, we assess the possible coevolution between the Rubisco catalysis and the type and effectiveness of CCMs present in six upper subtidal macroalgal species belonging to three phylogenetic groups of seaweeds. A wide diversity in the Rubisco kinetic traits was found across the analyzed species, although the specificity factor was the only parameter explained by the expressed Rubisco form. Differences in the catalytic trade-offs were found between Rubisco forms, indicating that ID Rubiscos could be better adapted to the intracellular O2 : CO2 ratio found in marine organisms during steady-state photosynthesis. The biophysical components of the CCMs also differed among macroalgal species, resulting in different effectiveness to concentrate CO2 around Rubisco active sites. Interestingly, an inverse relationship was found between the effectiveness of CCMs and the in vitro Rubisco carboxylation efficiency, which possibly led to a similar carboxylation potential across the analyzed macroalgal species. Our results demonstrate a coevolution between Rubisco kinetics and CCMs across phylogenetically distant marine macroalgal species sharing the same environment.
Keywords: Algas; CO2 concentrating mechanisms; CO2 fixation; Macroalgae; Photosynthesis; Rubisco kinetics; Seaweeds